Dynamics of the Foehn Mechanism in the McMurdo Dry Valleys of Antarctica from Polar WRF1. (12th November 2012) - Steinhoff, Daniel F.; Bromwich, David H.; Monaghan, Andrew
Abstract Foehn events over the McMurdo Dry Valleys (MDVs), the largest ice‐free region of Antarctica, promote glacial melt that supports biological activity in the lakes, streams, rocks and soils. Although MDVs foehn events are known to depend upon the synoptic‐scale circulation, the physical processes responsible for foehn events are unknown. A polar‐optimized version of the Weather Research and Forecasting model (Polar WRF) is used for a case study of a representative summer foehn event from 29 December 2006 to 1 January 2007 in order to identify and explain the MDVs foehn mechanism. Pressure differences across an elevated mountain gap upstream of the MDVs provide forcing for southerly flow into the western, upvalley entrance of the MDVs. Complex terrain over the elevated gap and the MDVs leads to mountain wave effects such as leeside acceleration, hydraulic jumps, wave breaking and critical layers. These mountain wave effects depend on the ambient (geostrophic) wind direction. Pressure‐driven channelling then brings the warm, dry foehn air downvalley to eastern MDV sites. Brief easterly intrusions of maritime air into the eastern MDVs during foehn events previously have been attributed to either a sea‐breeze effect in summer or local cold‐pooling effects in winter. In this particular case, the easterly intrusions result from blocking effects of nearby Ross Island and the adjacent Antarctic coast. Temperature variability during the summer foehn event, which is important for meltwater production and biological activity when it exceeds 0°C, primarily depends on the source airmass rather than differences in foehn dynamics.